2004
DOI: 10.1074/jbc.m406374200
|View full text |Cite
|
Sign up to set email alerts
|

Catalase-peroxidases (KatG) Exhibit NADH Oxidase Activity

Abstract: Catalase-peroxidases (KatG) produced by Burkholderia pseudomallei, Escherichia coli, and Mycobacterium tuberculosis catalyze the oxidation of NADH to form NAD ؉ and either H 2 O 2 or superoxide radical depending on pH. The NADH oxidase reaction requires molecular oxygen, does not require hydrogen peroxide, is not inhibited by superoxide dismutase or catalase, and has a pH optimum of 8.75, clearly differentiating it from the peroxidase and catalase reactions with pH optima of 5.5 and 6.5, respectively, and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 42 publications
6
86
0
1
Order By: Relevance
“…Our findings that the oxidase activity exhibited unique substrate and cofactor requirements, as well as reaction mechanisms, demonstrate that catalase oxidase activity is distinct from its previously recognized catalatic and peroxidatic activities. In this regard, the new enzymatic activity, which was oxygen-dependent, did not require the addition of hydrogen peroxide or any additional cofactors, similar to the oxidase activity found in catalase-peroxidase KatG (33). In addition, unlike the catalatic activity of catalase, which does not strictly follow classic Michaelis-Menten kinetics, presumably due to the high reaction rate and inactivation of the enzyme at high hydrogen peroxide concentrations (13,34), catalase oxidase activity was readily saturable and reversible.…”
Section: Discussionmentioning
confidence: 72%
“…Our findings that the oxidase activity exhibited unique substrate and cofactor requirements, as well as reaction mechanisms, demonstrate that catalase oxidase activity is distinct from its previously recognized catalatic and peroxidatic activities. In this regard, the new enzymatic activity, which was oxygen-dependent, did not require the addition of hydrogen peroxide or any additional cofactors, similar to the oxidase activity found in catalase-peroxidase KatG (33). In addition, unlike the catalatic activity of catalase, which does not strictly follow classic Michaelis-Menten kinetics, presumably due to the high reaction rate and inactivation of the enzyme at high hydrogen peroxide concentrations (13,34), catalase oxidase activity was readily saturable and reversible.…”
Section: Discussionmentioning
confidence: 72%
“…A multiplicity of methods has been employed to directly and indirectly assay INH activation, including the determination of INH oxidation to isonicotinic acid (9, 10), the HPLC assay of INH disappearance (11), the inactivation of InhA in a mixture of InhA and KatG (7,12,13,14), the HPLC detection of IN⅐NAD (4, 15), and the direct measurement of IN⅐NAD using its characteristic absorbance at 326 nm (6,7,12,15,16). Reports of INH activation in mixtures lacking an external oxidant (4,5,6,9,12,14,15) initially suggested that the peroxidatic process may not be required, but the mixtures of INH, NADH, and KatG would have supported NADH reduction of molecular oxygen to superoxide and low levels of H 2 O 2 (15) to activate the peroxidase reaction.…”
Section: Isonicotinic Acid Hydrazide (Isoniazid or Inh)mentioning
confidence: 99%
“…It is possible that in the pH ranges of ¡7.0 and .7.0, two different sets of amino acid residues of the protein play critical roles in catalysis. Another explanation is that at pH .7.0, rMjNox produces superoxide; certain Fe-containing Nox enzymes, which do not belong to the FDR family, exhibit such a behaviour (Singh et al, 2004). rMjNox did produce superoxide and the activity was elevated at pH .8.5.…”
Section: Discussionmentioning
confidence: 99%